MANAJEMEN PENGELOLAAN BIMBINGAN PRANIKAH DALAM MEWUJUDKAN KELUARGA SAKINAH MAWADDAH WA RAHMAH - Hamdi Abdul Karim (INSTITUT AGAMA ISLAM NEGERI METRO, 2019)
Marriage is a sunnatullah whose provisions have been outlined, by marriage can make a person's life more calm, directed, happy and peaceful. Marriage is a sacred bond that is woven by a man and woman, called holy because it is governed by the teachings of Religion and then legalized by the rules of State legislation, customs and others.Happiness is a goal in a marriage that is expected by every married couple. Happiness is manifested in the domestic life of Sakinah Mawaddah Wa Rahmah. communication that is not good in the household can be a cause of disharmony in family life for example the occurrence of disagreement between husband / wife. So pre-marital guidance is needed for prospective husbands and wives who want to foster household life in order to face difficulties in marriage wisely.Pre-marital guidance for prospective bride and groom is a form of government concern for the validity of the marriage to be performed. The implementation is mandated by the government to the Ministry of Religion in this case the Office of Religious Affairs (KUA) in every district. The implementation of pre-marital guidance can run well if it is paid attention to and is carried out with management which includes the elements involved in this pre-marital guidance. The elements include subjects, objects, materials, methods and media for premarital guidance.